Perspectives for clinical use of engineered human host defense antimicrobial peptides - María Eugenia Pachón-Ibáñez; Younes Smani; Jerónimo Pachón; Javier Sánchez‐Céspedes (2017)
Infectious diseases caused by bacteria, viruses or fungi are among the leading causes of death worldwide. The emergence of drug-resistance mechanisms, especially among bacteria, threatens the efficacy of all current antimicrobial agents, some of them already ineffective. As a result, there is an urgent need for new antimicrobial drugs. Host defense antimicrobial peptides (HDPs) are natural occurring and well-conserved peptides of innate immunity, broadly active against Gram-negative and Gram-positive bacteria, viruses and fungi. They also are able to exert immunomodulatory and adjuvant functions by acting as chemotactic for immune cells, and inducing cytokines and chemokines secretion. Moreover, they show low propensity to elicit microbial adaptation, probably because of their non-specific mechanism of action, and are able to neutralize exotoxins and endotoxins. HDPs have the potential to be a great source of novel antimicrobial agents. The goal of this review is to provide an overview of the advances made in the development of human defensins as well as the cathelicidin LL-37 and their derivatives as antimicrobial agents against bacteria, viruses and fungi for clinical use.